2006
DOI: 10.1210/me.2005-0327
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Specific Enhancer-Binding Protein/NKX2.1 Is Required for the Maintenance of Ordered Architecture and Function of the Differentiated Thyroid

Abstract: Thyroid-specific enhancer-binding protein (T/ebp)/Nkx2.1-null mouse thyroids degenerate by embryonic day (E) 12-13 through apoptosis whereas T/ebp/Nkx2.1-heterogyzgous mice exhibit hypothyroidism with elevated TSH levels. To understand the role of T/ebp/Nkx2.1 in the adult thyroid, a thyroid follicular cell-specific conditional knockout (KO) mouse line, T/ebp(fl/fl);TPO-Cre, was established that expresses Cre recombinase under the human thyroid peroxidase (TPO) gene promoter. These mice appeared to be healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 37 publications
4
97
0
1
Order By: Relevance
“…In the only other paper describing thyroid histology in a patient with an NKX2-1 mutation, no abnormalities were found [Maquet et al, 2009]. In contrast, the histological alterations found in our patient were very similar to those described in adult mice of the thyroid follicular cell-specific conditional KO mouse line Nkx2-1(fl/fl);TPO-Cre [Kusakabe et al, 2006], which suggested that NKX2-1 was required to maintain the normal architecture and function of the differentiated thyroid gland. Our results support a role for NKX2-1 in normal thyroid follicle structure in humans.…”
Section: Discussionsupporting
confidence: 78%
“…In the only other paper describing thyroid histology in a patient with an NKX2-1 mutation, no abnormalities were found [Maquet et al, 2009]. In contrast, the histological alterations found in our patient were very similar to those described in adult mice of the thyroid follicular cell-specific conditional KO mouse line Nkx2-1(fl/fl);TPO-Cre [Kusakabe et al, 2006], which suggested that NKX2-1 was required to maintain the normal architecture and function of the differentiated thyroid gland. Our results support a role for NKX2-1 in normal thyroid follicle structure in humans.…”
Section: Discussionsupporting
confidence: 78%
“…It is possible that impaired development of telencephalic vasculature in the Sey Dey mice is a result of impaired VEGF signaling. The role of Nkx2.1 and Pax6 in angiogenesis is not restricted to the CNS but seems more generalized and affects the lung, eye and cardiopulmonary system [39][40][41] .…”
Section: Compartmental Influences On Telencephalic Angiogenesismentioning
confidence: 99%
“…Because the Synapsin I promoter becomes active only in terminally differentiated neurons (Hoesche et al, 1993), Cre-mediated recombination deletes the Ttf1 gene only from postmitotic neurons. Mice carrying floxed Ttf1 alleles, produced by one of our laboratories, were described recently (Kusakabe et al, 2006). Crossing these two mutant lines generated hemizygote SynCre mice (SynCreϩ/Ϫ) carrying one floxed allele (Ttf1 flox/ϩ).…”
Section: Animalsmentioning
confidence: 99%
“…The primers used to detect the WT and floxed alleles (sense 5Neo2, 5Ј-TGCCGTGTAAACACGAGGAC-3Ј; and antisense 3Neo2, 5Ј-GACTCTCAAGCAAGTCCATCC-3Ј) were those described recently (Kusakabe et al, 2006). The PCR conditions used consisted of an initial activation step of 5 min at 95°C and 36 cycles as follows: 30 s of denaturing at 94°C, 30 s of annealing at 60°C, a 1 min extension at 72°C, and a final extension of 10 min at 72°C.…”
Section: Genotypingmentioning
confidence: 99%